Karakterisasi Morfologi, Anatomi dan Fisiologi Galur Mutan Gandum yang Ditanam di Dataran Rendah Tropik - Sari, Laela; Purwito, Agus; Sopandie, Didy; Purnamaningsih, Ragapadmi; Sudarmonowati, Enny (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2016)
Characterization of mutant wheat (Triticum aestivum L.) lines is a step on the breeding program to determine the beneficial characters for increasing the productivity in tropical lowland. The aim of this research was to obtain information on the variability of morphological, anatomical, and physiological characters that could be used as selection criteria and to obtain adaptive mutant lines of â€œAlibeyâ€ in tropical low altitude land. Research was conducted at the Experimental Farm of SEAMEO-BIOTROP in Bogor 250 m above sea level, from April to December 2013. Mutant lines of â€œAlibeyâ€ consisted of 16 M3 mutants resulted from treatments of EMS. LC50 of â€œAlibeyâ€ at 0.1% EMS for 60 minutes. Results showed that the mutant lines changed their morphological traits significantly, as indicated by the four characters i.e. long stem panicle (8 mutants), grain weight/panicle (1 mutant), weight of 100 seeds (4 mutants) and seed weight/plant (9 mutants). However, the mutant had no significant effect on the nine other characters, including: time of flowering, days to maturing, panicle length, plant height, number of tillers, panicle number, and leaf area. Anatomical characters namely leaf thickness and stomata size showed different values between â€œAlibeyâ€ mutant (AB-0.1.60-1-7-1) and the original Alibey. For the physiological characters there were significant differences among mutants with respect to the amount of proline and glucose levels. Proline level in the control plant was 4.15 ug/g BB, while that in mutant â€œAB-0.1.60-3-16-1â€ was 263.47 Âµg/g BB, and that in â€œAB-0.1.60-3-3-2â€ was 235.90 Âµ/g BB. Likewise, glucose level in control was 132.88 mg/ml, while in mutant â€œAB-0.1.60-3-16-1â€ was 181.48 mg/ml, and that in â€œAB-0.1.60-3-3-2â€ was 287.41 mg/ml. â€œAlibeyâ€ mutants should be selected based on two characters i.e. stem panicle length and seed weight/plant. Correlation analysis between panicle number and all other characters were not significant. Plant height significantly affected the grain weight/panicle and the grain weight/plant. It is expected that some of the mutants are adaptable to the tropical lowlands, so that the diversity of wheat germplasm in Indonesia is increased.